Peeling back the layers of childhood care entry in the United Kingdom: a dynamic mix of systematic reviews, public involvement, and administrative data insights. - Opoku, Richmond; Parker, Michael; Bristow, Dan; Kennedy, Natasha; Brophy, Sinead (International Journal of Population Data Science, 2025)
Objectives Placing children into out-of-home care is a critical issue with far-reaching social implications. Existing reviews have identified multi-level risk and protective factors that influence care entry; however, robust empirical quantification of these factors within the UK context remains limited. Methods A systematic review of published reviews was conducted to identify key factors, drawing predominantly on data from non‐UK contexts. Building on this evidence, an ongoing administrative data analysis is being conducted across Scotland, England, and Wales. The analysis employs descriptive statistics and Cox proportional hazards models to estimate the cumulative incidence of care entry by relevant characteristics. A distinctive element of this study is the incorporation of Public and Patient Involvement (PPI). Engagement with care-experienced children and parents affected by child removal has informed variable selection, study design, and interpretation of findings. Results Findings from the systematic review highlight significant associations between care entry and factors such as ethnicity, parental socioeconomic disadvantage, and wider community and systemic factors. Although the administrative analysis is ongoing, initial findings suggest that integrating multi-level factors could enhance the predictive accuracy of models for care entry. Preliminary results for Welsh and English data are anticipated by May 2025, with the analysis of Scottish data projected to extend into December 2025. Conclusions This integrated approach—merging systematic review evidence, administrative data analysis, and active PPI—demonstrates the potential to inform more comprehensive and preventative child welfare strategies. By examining the underlying determinants of care entry, this study aims to guide targeted policy interventions addressing inequalities in out-of-home care.